Factors Affecting Indonesian Customers’ Intention to Invest in Green Sukuk - Farhan NAUFAL; Sri DARYANTI (Communications of International Proceedings, 2020)
Climate change is occurring today due to the widespread exploitation of natural resources undertaken by humans in order to meet their needs. To deal with these problems, it is necessary we play an active role in preventing and/or dealing with climate change, such as using alternative energy sources and conducting environmentally-friendly activities. Responsible investment can support action taken against climate change. As a financing instrument in the Islamic economy, green sukuk can support such action by financing environmentally-friendly projects. This study aims to establish the factors that affect the intention to invest in green sukuk by using the theory of planned behaviour (TPB). The study respondents were 377 Indonesian citizens aged over 18 living in the country. The study found that religious values, issuers' reputation and knowledge have a positive and significant effect on attitude, and that subjective norms and perceived behavioural control have a positive and significant effect on the intention to invest in green sukuk.
Keywords: Green Sukuk; Intention; Structural Equation Modelling; Theory of Planned Behaviour.